2003
DOI: 10.1159/000073991
|View full text |Cite
|
Sign up to set email alerts
|

Helplessness as Predictor of Perceived Stigmatization in Patients with Psoriasis and Atopic Dermatitis

Abstract: Background: The experience of stigmatization is a problem frequently recognized in chronic skin diseases such as psoriasis and atopic dermatitis. The purpose of the study was to investigate a broad spectrum of physical, psychological and social predictors for perceived stigmatization in patients with psoriasis and atopic dermatitis. Patients and Methods: Stigmatization experience, demographic variables, age of onset, clinical status, physical symptoms of itch and fatigue, the impact of the disease on daily lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
126
5
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(149 citation statements)
references
References 18 publications
12
126
5
6
Order By: Relevance
“…In order to aid intervention development, a broad understanding of associated risk factors is needed, to be able to identify risk populations and focus points for interventions. The literature suggests several potential sociodemographic predictors of perceived stigmatization in psoriasis, such as lower age, 7 being female 5 and lower education. 7 Secondly, disease-related variables such as higher disease severity, longer disease duration, greater cosmetic involvement and greater impact of the condition on daily life may be relevant.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In order to aid intervention development, a broad understanding of associated risk factors is needed, to be able to identify risk populations and focus points for interventions. The literature suggests several potential sociodemographic predictors of perceived stigmatization in psoriasis, such as lower age, 7 being female 5 and lower education. 7 Secondly, disease-related variables such as higher disease severity, longer disease duration, greater cosmetic involvement and greater impact of the condition on daily life may be relevant.…”
mentioning
confidence: 99%
“…The literature suggests several potential sociodemographic predictors of perceived stigmatization in psoriasis, such as lower age, 7 being female 5 and lower education. 7 Secondly, disease-related variables such as higher disease severity, longer disease duration, greater cosmetic involvement and greater impact of the condition on daily life may be relevant. [7][8][9]13,21,22 General ways in which patients deal with a chronic condition, such as heightened helplessness regarding the disease and its consequences, and lower disease acceptance have also been found to be predictive.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the proportion of patients that suffer from 'the experience of stigmatization' is far greater. Indeed, Lu et al [13] found that about 80 percent of patients with psoriasis and atopic eczema felt stigmatized by others because of their skin disease at least once, 30 percent of which severely. The experience of stigmatization is one of the strongest determinants of perceived restrictions in everyday life [14,15] and can lead to decreased self-confidence and feelings of shame.…”
Section: A U T H O R ' S C O P Y N O T F O R S a L E O R D I S T R I mentioning
confidence: 99%